O trabalho do caminhoneiro: entre a malha rodoviária e a saúde mental - Moreira, Jansen Souza (2020)
Truck drivers are responsible for more than half of cargo transportation in Brazil nowadays, an essential profession for maintaining the distribution base in the capitalist production-distribution-consumption tripod. However, they face adverse and often precarious work conditions, which can lead to mental wear and, consequently, mental illness. From a psychosociological perspective, this research aimed to analyze the work experiences reported by truck drivers, and the possible repercussions on mental health. About the instruments, it was used: General Health Questionnaire - GHQ-12; Epworth Sleepiness Scale - ESE; Interview; and Sociodemographic Questionnaire. For an analysis of quantitative data in the free software GNU PSPP (1.0.1), descriptive statistics were performed (measures of central tendency, such as mean and mode, dispersion measures, such as standard deviation, and position measures, such as quartiles), Spearman's correlation, chi-square (X²) and simple linear regression; for qualitative data, a content analysis (thematic) technique was used. The results show evidences of mental wear, considering the complaints that are mostly reported: sleep problems, sociolabor difficulties, family distance, and several aspects related to working conditions; this is a moderate wear, when considering the scores of the two factors in parallel, Reduction of Self-Efficiency and Emotional Stress and Depression, of the QSG-12, both close to the midpoint of the scale. It is also considered that these negative aspects are counterbalanced by reported factors that promote well-being, such as affective identification with the profession, acquisition of new experiences and obtaining income for family support despite low education, all those that need to be highlighted and promoted as a preventive possibility of aggravations in workers' mental health. Such findings can assist in the planning of educational and psychological interventions reinforced to social support, and increase in the search of truck drivers for preventive health services. Subsequent research may include organizational support within the scope of the causal link in mental health and work, in order to broaden the understanding of the processes adjacent to these constructs.